Comparative Analysis of the Crime of Adultery Based on the Old Criminal Code and the New Criminal Code to Realize Justice - Darsono, Ahmad Bagas Dwi; Guntara, Deny; Abas, Muhamad (PT. Anagata Sembagi Education, 2024)
Law number 1 of 2023 was prepared as an update of the old product, namely the Netherlands Heritage Fund. Various new paradigms of legal protection are part of the preparation of the draft of Law number 1 of 2023. However, at the same time, the protection of commercial sex workers (PSK) is still limited to efforts to provide a deterrent effect on those who allow prostitution to occur. In fact, the solution to the problem of prostitution should be solved systematically with lex specialis who raises issues involving prostitution. Meanwhile, the weakness of Law number 1 of 2023 is that it has not solved the core problem of brutal and inhumane social justice in prostitution. However, Law number 1 of 2023 has at least stopped the criminalization of prostitution. This research is prepared by normative juridical methods and reviews the law in depth based on the editorial and context of legal products of Law number 1 of 2023 on the basis of research to find.